2020
DOI: 10.3389/fped.2020.00473
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Primary and Secondary Pediatric Mucoepidermoid Carcinoma of the Head and Neck

Abstract: Objectives: Secondary mucoepidermoid carcinoma (MEC) of the head and neck is occasionally observed in childhood cancer survivors. The goal of this research was to compare the demographic and pathologic characteristics, as well as survival between primary and secondary MEC in children and adolescent patients. Methods: Pediatric patients (younger than 19 years old) with surgically treated MEC of the head and neck were retrospectively enrolled at the Affiliated Children's Hospital of Zhengzhou University and divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…According to the literature, there is a lack of research dealing with malignant salivary tumors in children, mostly dated research or case reports [17,[29][30][31]. In accordance with Cockerill et al [25], who identified 56 patients (<18 years old) with malignant salivary gland tumors over a period of 60 years, in our findings, a greater prevalence of mucoepidermoid carcinoma was reported among the malignant group and the parotid gland was commonly involved.…”
Section: Oncologic Disorderssupporting
confidence: 84%
“…According to the literature, there is a lack of research dealing with malignant salivary tumors in children, mostly dated research or case reports [17,[29][30][31]. In accordance with Cockerill et al [25], who identified 56 patients (<18 years old) with malignant salivary gland tumors over a period of 60 years, in our findings, a greater prevalence of mucoepidermoid carcinoma was reported among the malignant group and the parotid gland was commonly involved.…”
Section: Oncologic Disorderssupporting
confidence: 84%
“…8,25 One thousand four hundred and twenty-five (93.1%) patients with malignant disease were alive at their last follow-up, and 104 (6.9%) were dead. Six patients had a different cause of death, 6,8,26,27 but this information was not available for 680 (30.6%) cases.…”
Section: Description Of the Individual Studiesmentioning
confidence: 99%